'Chosen Comrades': Yeats's Romantic Rhymes. Issue 2 (July 2017) - Callaghan, Madeleine
Abstract : Yeats's acute sense of the poet's labour, a labour that makes rhyme one of those 'befitting emblems of adversity' ('My House', Meditations in Time of Civil War, 30) energises his poetry. Rather than constricting poetry, rhyme can engender, if paradoxically, a kind of freedom for the poet; Yeats's choice of form reveals his Romantic influences while demonstrating his independence. Encompassing examples from Blake, Byron, Keats, and Shelley, this essay shows how Yeats learns from his chosen influences even as his mastery over their forms sponsors his 'ghostly solitude' ('Nineteen Hundred and Nineteen', 40). From his experimentation with trimeter to ottava rima and terza rima, Yeats's formal dexterity places rhyme centre stage as he emerges as a resolutely individual poet.